P689 The effect of nutritional therapy on bone mineral density and bone metabolism in paediatric Crohn's disease. (25th January 2019) - Lev-Tzion, R; Ben-Moshe, T; Abitbol, G; Ledder, O; Levine, A; Peleg, S; Millman, P; Shaoul, R; Shamaly, H; On, A; Kori, M; Assa, A; et al.
Abstract: Background: Childhood is a critical time for accrual of bone density, which peaks at age 18–20 years. Both the inflammatory burden of CD and corticosteroid therapy have a negative effect on bone density, hence exclusive enteral nutrition (EEN) is the preferred treatment option to induce remission. We aimed to explore the effect of nutritional therapy on bone health in paediatric CD. Methods: This was a planned sub-study of a randomised controlled trial of children with mild-to-moderate CD who were randomised to receive either 6 weeks of EEN followed by 6 weeks of 25% PEN with free diet or 6 weeks of 50% partial enteral nutrition (PEN) with a Crohn's disease exclusion diet (CDED) followed by 6 weeks of 25% PEN+CDED. For the aim of this ancillary study, we measured bone mineral density (BMD) by DXA scan at baseline and Week 24 (total body less head adjusted for age and height). In addition, bone formation was measured at baseline, Week 12 and Week 24, by the serum biomarker C-Propeptide of Type I Procollagen (CICP) and bone resorption was measured by serum Type I Collagen N-Telopeptide (NTX). Results: Repeated BMD was completed for 23 children and showed BMD < -1 SD in 17 (74%) and BMD < −2 in 7 (30%) at baseline. DXA results did not improve at Week 24 (BMD -1.52 ± 0.72 at baseline vs. −1.65 ± 0.81 at Week 24; p = 0.36). The change was also not significant in analysis of the individual treatment arms. In the subset of patients who achieved remission at Week 12, DXA scores did not worsen but did not improve either (median change of −0.01, IQR 0.17--0.26); compared with patients not in remission, the difference was not significant. Serial biomarkers were available for 29 children. Median CICP improved from 130 ng/ml (IQR 3–1 189-106)) at baseline to 223 (258-143)) at Week 12 and 189 (227–145) at Week 24 ( p = 0.016 for both). Median NTX remained unchanged, from 36 nmol bone collagen equivalents/l (IQR 58–30) at baseline to 50 (66–28) at Week 12 ( p = 0.45) and 37 (66–24) at Week 24 ( p = 0.37). Analysis of individual treatment arms was not possible for the bone biomarkers due to small sample size. Conclusions: BMD did not improve in children with active CD treated with nutrition. However, CICP, a much more responsive and sensitive marker of bone formation increased significantly, raising the possibility that bone improvement is slow and should be further examined in longer-term studies.